Benzocyclobutene resin with m-carborane cages and a siloxane backbone: a novel thermosetting material with high thermal stability and shape-memory property. Issue 29 (4th March 2016) - Huang, Xin; Zhang, Qiuhong; Deng, Guoqing; Meng, Zhen; Jia, Xudong; Xi, Kai
Abstract : A simple and effective way to synthesize carborane-containing benzocyclobutene resin with excellent performances. Abstract : In this paper, we report the design, synthesis and properties of novel cross-linked benzocyclobutene resin with m -carborane cages and a siloxane backbone. The synthesis process of the m -carborane derivative containing the benzocyclobutene functional group was simple and efficient. 1 H, 13 C, and 29 Si NMR confirmed the structure of the dibenzocyclobutene-functional m -carborane (DBMC). The novel polymer film was readily fabricated through ring-opening polymerization of the benzocyclobutene unit. Differential scanning calorimetry (DSC) and FT-IR were used to study the curing behavior. Thermogravimetric analysis (TGA) showed that the cured film had outstanding thermal stability. The cross-linked film also exhibited good shape-memory property, and had the capacity to address challenges in advanced aerospace. The boron in the cured DBMC was abundant and showed homogeneous distribution at the microscale. These data imply that the cured DBMC is suitable for use as a neutron shielding material, especially in aerospace applications such as neutron shielding garments.